Inhibition of Platelet Thrombosis Using an Activated Protein C-loaded Stent: In Vitro and In Vivo Results - Foo, Roger S.-Y.; Gershlick, Anthony H.; Hogrefe, Kai; Baron, Julia H.; Johnston, Thomas W.; Hussey, Amanda J.; Garner, Ian; de Bono, David P. (Thrombosis and Haemostasis, 2000)
In high-risk and complicated coronary intervention, the risk of acute closure is unpredictable. Thrombus and platelet deposition at the intervention site may also have further effects on subsequent restenosis. In vivo infusion of activated protein C has previously been shown to achieve potent anticoagulation without any haemostatic side effects. We now evaluated the in vitro and in vivo efficacy of polymer-coated coronary stents loaded with purified rabbit Activated Protein C (APC). By measuring 125I-fibrinogen/fibrin deposition APC-loaded stent-wires were antithrombotic compared to albumin-loaded, inhibited-APCloaded, plain polymer-coated and stainless steel stent-wires. In a balloon injury rabbit iliac artery model, APC-loaded stents did not occlude (0/14) compared to plain stents (9/15) and BSA-loaded stents (2/4). Relative 111In-labelled platelet deposition showed a similarly significant degree of inhibition. In conclusion, APC-loading could render stents significantly less thrombotic. Whether an effective antithrombogenic stent like this effectively reduces restenosis rates warrants further evaluation.
Keywords: Activated protein C; stents; thrombosis; platelet deposition